Metal treatment for fibrous substrates, process for treating fibrous substrates, and filter media having treated fibrous substrates - Patents.com
By acid leaching and ion exchange, glass fibers are treated with divalent and trivalent metal cations to enhance their affinity for airborne virus particles, improving capture and inactivation efficiency in HEPA filters.
Patent Information
- Application Number
- JP2024538477
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-07
- Filing Date
- 2022-12-27
- Publication Date
- 2025-01-17
AI Technical Summary
Existing glass HEPA filter media struggle to effectively incorporate metal ions without compromising particle removal properties, necessitating a need for efficient processes to enhance the affinity of fiber substrates for airborne virus particles.
A method involving acid leaching to create acidic ion exchange sites on glass fibers, followed by immersion in a salt solution containing divalent and trivalent metal cations, which are deposited onto the fibers through ion exchange, ensuring the metals are present in ionic form on the fiber surfaces to increase affinity for virus particles.
The treated fibers demonstrate enhanced affinity for airborne virus particles, leading to improved capture and inactivation efficiency, with metal ions evenly distributed throughout the filter media, maintaining filtration performance and reducing viral infectivity on the surface.
Smart Images

Figure 2025501139000001_ABST
Abstract
Description
[Technical field]
[0001] (Statement of priority) This application claims priority to U.S. Provisional Patent Application No. 63 / 266,208, filed December 30, 2021, which is incorporated by reference in its entirety.
[0002] FIELD OF THEINVENTION The present invention relates generally to treatments for glass fibers, and more specifically to treatments that impart increased activity in capturing airborne viral particles as compared to the surface of a glass fiber filter substrate, as well as methods of applying such treatments. [Background technology]
[0003] The coronavirus known as "COVID-19" has caused a global pandemic that has resulted in a huge number of affected individuals requiring hospitalization and, in many cases, resulting in death. Thus, the unexpected pandemic has highlighted the need for physical or chemical agents that can capture, inactivate, or destroy viruses such as the Covid-19 virus.
[0004] Coronaviruses are a group of viruses that usually cause mild illnesses such as the common cold. However, certain species of coronaviruses can infect the lower respiratory tract and cause severe illnesses such as pneumonia or bronchitis. Most people will be infected with a coronavirus at some point in their lives, but the vast majority of these infections are harmless. The novel coronavirus that causes the COVID-19 disease is a notable exception.
[0005] Coronaviruses have an extremely large single-stranded RNA genome 26,000-32,000 bases or RNA "letters" long. Coronavirus particles are surrounded by a fatty outer layer called an envelope and typically appear spherical when viewed under an electron microscope, with a crown or "corona" of club-shaped spikes on their surface.
[0006] Thus, the unexpected pandemic has highlighted the need for physical or chemical agents that can capture, inactivate, or destroy viruses such as the COVID-19 virus.
[0007] High-Efficiency Particulate Air (HEPA) and Ultra-Low Particulate Air (ULPA) filtration can be used to remove airborne viral particles from the air. The ULPA standard requires the removal of 99.9995% of particles up to 1.2 micrometers. Both HEPA and ULPA filters consist of countless tiny strands of randomly arranged glass microfibers, typically an alkali borosilicate glass composition for HEPA and a low boron composition for ULPA in cleanroom applications.
[0008] Fiberglass wet-laid media is found in high pressure hydraulic filtration because fiberglass is incompressible and offers excellent dirt holding capacity. Fiberglass fibers can be manufactured very fine, even sub-micron in diameter, making it the material of choice for HEPA filters for clean rooms, coalescing media, hospital and other medical air filtration, and certain laboratory filters.
[0009] Existing glass HEPA filter media are known to effectively remove airborne viral particles, but it is difficult to incorporate metal ions into the glass fiber substrate without adversely affecting its particle removal properties.
[0010] Metal ions, particularly antiviral metal ions, are typically deposited in glass via ion exchange, often in a molten salt medium, followed by a high temperature heat treatment to initiate solid ion exchange and diffusion of the active metal ions into the glass. The resulting glass articles are typically used for antiviral glass surfaces for touchpads, laptop computers, and smartphone screens, but this process is not compatible with the production of microglass fibers used in air filtration.
[0011] Thus, there remains a need for an effective and efficient process for treating fiber-based substrates, such as fiberglass, to increase the affinity of the fibers for airborne viral particles. Summary of the Invention
[0012] The present invention provides a novel method for treating fibrous substrates, such as glass fiber filter media, to create a surface with increased affinity for airborne virus particles. The process treats the surface of the fibrous substrate to increase the amount of divalent and trivalent metals on the surface of the fibers in the substrate. The fibers may be subjected to an acid leaching step to generate acidic ion exchange sites. This acid leaching step may be omitted, if desired, for more chemically reactive glasses with engineered biosolubility properties, and in some cases for more conventional glass compositions with higher levels of alkali in the composition, such as B- or C-glass microfibers. The acidic ion exchange sites of the fibrous substrate are then exchanged by immersion, spraying, or dipping in a neutral or weakly alkaline salt solution containing cations of divalent and trivalent metals. This ion exchange process may be advantageously accomplished at the wet end of the filter media papermaking machine in a mixing tank before the headbox, in the headbox immediately before wet laying onto the moving forming fabric, or after wet laying and before drying, before, during, or after adding binder resin to the formed media. This ensures that the metal ions are present in ionic form at the very surfaces that come into contact with airborne virus particles during use.
[0013] Thus, in at least one embodiment, the present invention can be characterized as providing a process for treating a fiber substrate comprising glass fibers, introducing the fiber substrate into a salt solution, the salt solution comprising divalent metal cations, trivalent metal cations, or a combination thereof, depositing the metal cations on the fiber substrate, and drying the fiber substrate after the metal cations have been deposited, the divalent metal cations and the trivalent metal cations being selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, La3+, Bi3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, Lu3+.
[0014] Divalent and trivalent metal cations may be selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, and Ba2+.
[0015] Divalent and trivalent metal cations can be deposited by ion exchange. Ion exchange can occur with protons on the fibrous substrate. Ion exchange can occur with monovalent metal cations on the fibrous substrate.
[0016] Divalent and trivalent metal cations can be deposited by entanglement in the fibrous substrate.
[0017] The process may further include increasing the amount of SiOH species on the glass fibers. The amount of SiOH may be increased by acid leaching. The acid leaching may be performed prior to introducing the fiber substrate into the salt solution. The acid leaching may be performed simultaneously with introducing the fiber substrate into the salt solution.
[0018] The amount of divalent metal cations and trivalent metal cations on the fibrous substrate that can be increased is at least 0.001% by weight of the fibrous substrate.
[0019] The amount of divalent metal cations and trivalent metal cations on the fibrous substrate may be at least 0.005% by weight of the fibrous substrate.
[0020] The amount of divalent metal cations and trivalent metal cations on the fibrous substrate may be 0.001 to 3.0% by weight of the fibrous substrate.
[0021] In another aspect, the invention may be characterized as providing a filter media substrate comprising glass fibers that have been treated to increase the amount of divalent cations, trivalent cations, or both by at least 0.001% by weight, wherein the divalent and trivalent metal cations are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, Bi3+, La3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, and Lu3+.
[0022] Divalent and trivalent metal cations may be selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, and Ba2+.
[0023] The divalent metal cations and trivalent metal cations may be present in an amount of 0.005 to 3.0% by weight of the filter medium substrate.
[0024] The divalent metal cations and trivalent metal cations may be present in an amount of 0.01 to 3.0% by weight of the filter medium substrate.
[0025] The divalent metal cations and trivalent metal cations may be 0.05 to 3.0% by weight of the filter medium substrate.
[0026] The divalent metal cations and trivalent metal cations may be 0.1 to 3.0% by weight of the filter medium substrate.
[0027] The divalent metal cations and trivalent metal cations may be 0.15 to 3.0% by weight of the filter medium substrate.
[0028] Further aspects, embodiments and details of the invention, all of which may be combined in any manner, are set out in the following detailed description of the invention. [Brief description of the drawings]
[0029] One or more exemplary embodiments of the invention are described below in conjunction with the following drawings. [Figure 1] FIG. 2 illustrates a processing process according to an embodiment of the present invention. [Diagram 2] FIG. 1 illustrates a papermaking process according to an embodiment of the present invention. [Diagram 3] 1 is an image showing glass fibre on the left and zinc deposited on the glass fibre on the right. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] As described above, the process deposits divalent and / or trivalent metal cations onto the fibrous substrate. The fibers of the fibrous substrate contain acidic ion exchange sites that have had acid protons exchanged with divalent or trivalent metal cations or monovalent cations exchanged with divalent or trivalent metal cations. This treatment can be performed on hydrophilic and hydrophobic substrates (filters, fabrics, other target surfaces). Compared to untreated surfaces, the treated surfaces are believed to have an increased affinity for removing airborne virus particles.
[0031] The name of the virus responsible for the 2019-2020 pandemic is Severe Acute Respiratory Syndrome Coronavirus 2, or SARS-CoV-2. The name of the disease caused by SARS-CoV-2 is COVID-19, which stands for "coronavirus disease 2019." Often, the terms for the virus and disease names are used interchangeably. For purposes of this application, "coronavirus pandemic" and similar expressions may be used, where "coronavirus" is understood to be an abbreviation for "coronavirus disease" (specifically COVID-19).
[0032] SARS-CoV-2 is a large enveloped virus. Its lipid envelope makes it particularly sensitive to biocides. For the purposes of this application, "antiviral" means a substance that kills the "COVID-19-causing virus" or the "COVID-19 virus."
[0033] This application provides a novel approach for depositing metals on various substrates, especially fiberglass, that can be incorporated into existing filter technologies, especially high efficiency and HEPA filters. Antiviral HEPA filters are expected to play a key role in ensuring the safety of employees, customers, and students as they return to indoor environments. Importantly, the technology or process resulting from this invention is amenable to existing fiber and papermaking technologies and can be easily scaled up to meet manufacturers' requirements. This process can be used to deposit a wide variety of metals and is expected to be easily incorporated into existing wet lamination media manufacturing processes.
[0034] With these general principles in mind, one or more embodiments of the invention are described, with the understanding that the following description is not intended to be limiting.
[0035] 1, the process 100 includes six main steps: providing a fibrous substrate 102, acid leaching the fibrous substrate 104, introducing a metal salt solution 106, adjusting the pH of the metal salt solution 108, optionally decanting or filtering and washing the treated substrate 110, and drying the substrate 112. Also shown are incorporating the fibrous substrate into a filter medium 120 and incorporating the treated fibrous substrate into a filter medium 130.
[0036] These steps are described below with the understanding that terms such as "first," "second," "third," and "fourth" do not indicate a particular order and should not be inferred unless explicitly stated.
[0037] Fiber Base Material In a first step 102 of the process 100, a fibrous substrate is provided. The fibrous substrate can include fibers typically used in filter media, such as fiberglass. In a particular embodiment, the fibrous substrate is borosilicate glass.
[0038] The fibers 10 may be any type of fiber typically used in filter media, such as glass fibers. For example, the fiber substrate may be A-glass fibers, B-glass fibers, C-glass fibers, D-glass fibers, E-glass fibers, ECR-glass fibers, T-glass fibers, S2-glass fibers, M-glass fibers, and mixtures thereof. Biosoluble glasses, such as low Al2O3 glasses with high B2O3 and either high Na2O+K2O content or high CaO+MgO content.
[0039] For example, the fiber substrate may be a biosoluble glass such as A-glass, B-glass, C-glass, or a low Al2O3 glass with high B2O3 and either high Na2O+K2O content or high CaO+MgO content. In a preferred embodiment, the fiber substrate is a B- or C-glass borosilicate, or a biosoluble microglass glass such as Johns Manville 253, 475, 481, or 902 glass. C-04-F and B-04-F glass microfibers are manufactured by Unifrax Specialty Fibers, and JM 481 is manufactured by Johns Manville.
[0040] C-04-F contains 63.0-67.0 SiO2; 4.0-7.0 B2O3; 14.0-17.0 Na2O; and 3.0-5.0 Al2O3. B-04-F contains 55.0-60.0 SiO2; 8.0-11.0 B2O3; 9.5-13.5 Na2O; and 4.0-7.0 Al2O3. JM 481 glass microfiber contains 60.8 wt% SiO2; 11.4 wt% B2O3; 9.1 Na2O; and 2.0 Al2O3.
[0041] The fibrous substrate may be provided in dry form, in a suspension, or otherwise dispersed in a liquid medium.
[0042] Acid leaching In the second step 104, an optional acid leaching is performed. The glass microfibers may first be treated with acid in an acid leaching step. This step may be useful for fiber substrates that initially have low hydrophilicity, since the acid treatment substantially increases the hydrophilicity by generating SiOH species on the glass surface. In the illustrated embodiment, nitric acid is used to exchange the alkali and alkaline earth cations of the fiber substrate with protons, as well as to leach some of the B2O3 and Al2O3 oxides from the glass. Both processes generate acidic SiOH species on the glass surface.
[0043] In the illustrated embodiment, nitric acid is used to exchange the cations of the fiber substrate with protons. However, in other embodiments, any strong acid can be used, including hydrohalic acids such as HF or HCl, or carboxylic acids such as acetic acid. If used, the acid leaching step may be performed in a stirred tank just before the headbox of the paper machine, followed by decanting the leachate and resuspending the glass fibers in water before pumping the fiber furnish to the headbox. In some cases, decanting / reslurrying may not be necessary if an acidic paper furnish is desired for wet lamination.
[0044] Introduction of divalent / trivalent metal ions Referring to the third step 106, in the process 100, the fibrous substrate is introduced into a solution containing divalent and / or trivalent metal cations.
[0045] A metal salt solution is prepared. In an illustrated embodiment, the metal salt comprises a cation that is a divalent or trivalent cation. Exemplary metal cations include Cu2+, Ag2+, Zn2+, Fe2+, Fe3+, Ni2+, Sn2+, Mn2+, Co2+, Co3+, Ga3+, Bi3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, La3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, Lu3+. The cations in the solution may be derived from salts such as nitrates, acetates, chlorides, or sulfates that dissociate in a suitable solvent (water).
[0046] Although some metals have been reported to have antiviral properties, it is believed that increasing the amount of divalent and / or trivalent metal cations on the fiber increases their affinity for airborne particles. Thus, the salt solution may have a mixture of metal cations including at least one first cation selected from Cu2+, Ag2+, Zn2+, Bi3+, Fe2+, Fe3+, Ni2+, Sn2+ and at least one second cation selected from Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, La3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, Lu3+. It is contemplated that the at least one second cation is selected from Mg2+, Ca2+, Sr2+, Ba2+. In some embodiments, one salt solution containing both the first and second cations may be provided, while in other embodiments, a first solution containing one of the first or second cations may be used, and then a second solution having the other of the first or second cations may be used.
[0047] It is further contemplated that the first fibers are treated with a first cation and the second fibers are treated with a second cation. The two types of fibers (each treated with a different cation) may be mixed in equal or unequal amounts to form the filter media. Thus, the filter media has fibers that are rich in the first cation and fibers that are rich in the second cation.
[0048] The substrate can be introduced into the salt solution by any number of processes, for example, by immersing the substrate in the metal salt solution, by brushing the metal salt solution onto the substrate, or by spraying the metal salt solution onto the substrate. For example, treatment can be accomplished by adding the metal salt solution to the paper machine headbox or an upstream wet end tank at an effective time between 0 and 60 minutes prior to wet-laying the glass fiber media, and then, optionally, decanting or filtering the spent solution from the treated fibers prior to sheet formation. Another possible treatment operation is to pump or spray the metal ion exchange solution immediately after the wet-laid glass media is formed onto the forming fabric at one or more of the following times: immediately prior to addition of the resin binder, in combination with addition of the resin binder, or immediately after the resin binder is added. These processes are known in the papermaking art.
[0049] The mode and mechanism of attachment may vary depending on the properties of the metal ion and the fibrous substrate. For example, in some cases, the metal may be bound to the fibrous substrate by ion exchange with, for example, protons or monovalent cations on the surface of the fiber. In some cases, the metal ion may be entangled with the fibers in the fibrous substrate.
[0050] The exact process by which the metal is deposited on the substrate is not important, so long as the divalent or trivalent metal is secured for a commercially suitable period of time (which may vary for different materials).
[0051] Adjusting the pH of metal salt solutions 1, a fourth step 108 of the process 100 includes adjusting the pH of the metal salt solution, which is contemplated to occur before, after, or during the introducing step 106.
[0052] For example, while the fibrous substrate is in the metal salt solution, the pH is adjusted to maximize deposition of divalent and / or trivalent metals onto the fibrous substrate. In a preferred embodiment, the pH is adjusted to provide a pH greater than 5.0. Preferably, the pH is adjusted to between 5.2 and 11.5, more preferably between 7.0 and 11.0. In an illustrated embodiment, the pH adjustment is performed by adding ammonium hydroxide to the solution. Other bases, such as dilute sodium hydroxide, may be used.
[0053] In the suspension, the metal ions are exchanged with the protons of the acidic functional groups and with the residual alkali cations on the fibrous substrate. After a sufficient time for the exchange to occur, the suspension containing the fibrous substrate containing the divalent and / or trivalent metal ions forms a treated fibrous substrate.
[0054] Alternatively, instead of metal ion deposition occurring prior to the pH adjustment step, it is contemplated that metal ion deposition occurs during the pH adjustment step. For example, the substrate can be immersed in a weakly acidic solution containing metal ions to exchange the metal ions for protons or residual alkali cations.
[0055] Washing The fifth step in the process 100 is an optional washing step 110. In the illustrated embodiment, ammonium hydroxide is used to wash the treated fiber substrate or the formed wet layer metal deposition media. In other embodiments, other solvents, such as purified water and / or deionized water, may be used.
[0056] Drying The sixth step in the process 100 is to dry the treated substrate 112. In this step, the suspending medium evaporates, leaving behind the treated fibrous substrate and any unattached metal ions attached to the substrate surface, resulting in a dry treated substrate.
[0057] Dewatering and drying may be accomplished by vacuum dewatering and / or mechanical pressing, typically performed on the forming portion of the forming fabric, followed by removal from the forming fabric and continuous conveying through infrared drying, hot air drying, drying on heated rollers, or other drying unit operations known in the art. In the illustrated embodiment, drying of the treated fibrous substrate is accomplished at a temperature of 50-150 degrees Celsius.
[0058] Optionally, the washing and drying steps may be omitted.Following metal deposition, the treated fibrous substrate may be incorporated into a filter medium, as shown in process 100 of FIG.
[0059] Paper manufacturing The process of incorporating 120 the fibrous substrate into a filter medium and 130 the treated fibrous substrate into a filter medium are shown in Figure 1. It is envisioned that metals can be deposited onto the fibrous substrate to form a treated fibrous substrate, which is then incorporated into the filter medium via a wet lay-up process. It is also envisioned that the fibrous substrate can be incorporated into the filter medium via a wet lay-up process, after which divalent and trivalent metal ions can be deposited onto the fibrous substrate to form the treated fibrous substrate.
[0060] 2 illustrates an embodiment of a wet lamination process 300. The wet lamination process includes a pre-headbox area A, a headbox area B, a wet lamination area C, a binder area D, a rolling area E, a drying area F, and a post-drying area G. The pre-headbox area includes a first pre-mix tank 302a and a second pre-mix tank 302b.
[0061] In the pre-headbox zone A, a first fibrous substrate 301a is provided and a first divalent / trivalent metal component 301b is introduced to the fibrous substrate. In the second pre-mix tank 302b, a second fibrous substrate 301c can be introduced to a second divalent / trivalent metal component 301d.
[0062] Headbox pre-mix 302 produces fiber slurry 304. The fiber slurry is sent to a headbox 306, which is used to apply the fiber slurry to a wet-laid paper machine. The wet-laid paper machine includes a suction box 308 to draw liquid downwards, and an inclined wire 310. A binder 312 is then applied to the wet-laid fibers. A nip roll press 314 compresses the web, and a dryer 316 removes excess water. Rollers 318 are then used to store the media. Post-drying 320 may include further coatings or treatments.
[0063] In certain contemplated embodiments, divalent / trivalent metal cations may be introduced to the fibrous substrate in the pre-headbox zone A, the headbox zone B, the wet-laid zone C, the binder zone D, the rolling zone E, and the post-dry zone G.
[0064] The media may be formed by a traditional type of paper machine headbox called a Fourdrinier headbox. Media made from long synthetic fibers and difficult to disperse furnishes are produced in headboxes designed specifically for this purpose. The two most common are the Rotoformer® headbox and the inclined wire headbox. Glens Falls Interweb (GFI) of Glens Falls, New York manufactures both. The Rotoformer® forms the sheet on a rotating drum covered with wire. The inclined wire headbox (known as the Delta Former®) forms the sheet on the inclined surface of the wire as it passes through the pound.
[0065] Contemplated embodiments include the divalent / trivalent metal being introduced to the fibrous substrate at various points during the papermaking process. For example, the divalent / trivalent metal can be introduced to the fibrous substrate at one or more of the following unit operations of the papermaking process: the wet end mixing tank, machine chest, headbox, or binder impregnation section of a papermaking machine selected from the group consisting of a Fourdrinier, twin wire papermaking machine, Rotoformer®, Delta Former®, or other tilt type papermaking machine.
[0066] For example, it may be desirable to further adjust the fiber slurry chemistry to improve substrate formation in the presence of divalent / trivalent metal deposition solutions of increased ionic strength by adding charged and / or neutral retention aids such as cationic and anionic polyacrylamides of various charge densities and molecular weight distributions, polyethyleneimine polyelectrolytes, starches, colloidal clays, aluminas, and silicas, as well as neutral polyethylene oxides of various molecular weight distributions known in the art.
[0067] It should be appreciated that any suitable method for making the glass fiber slurry may be used. In some cases, divalent / trivalent metal cations and any additional additives are added to the slurry to facilitate processing. The temperature and pH may also be adjusted to an appropriate range. In some embodiments, the temperature and pH of the slurry are maintained. In some cases, the temperature and pH are not actively adjusted.
[0068] In some embodiments, the wet-laid process uses equipment similar to conventional papermaking processes, including hydropulpers, formers or headboxes, dryers, and optional converters. For example, a slurry may be prepared in one or more pulpers. After proper mixing of the slurry in the pulper, the slurry may be pumped to a headbox where it may or may not be combined with other slurries or may or may not have additives added. The slurry may be diluted with additional water to bring the final concentration of fibers to a suitable range.
[0069] In some embodiments, the process then includes introducing a binder into the preformed glass fiber web. In some embodiments, the different components contained in the binder (e.g., soft binder, optional hard binder), which may be in the form of separate emulsions, are added to the glass fiber web using a suitable technique as the glass fiber web passes along a suitable screen or wire. One or more divalent / trivalent metals may also be suitably added to the glass fiber web, either together with the binder or independently of the binder. In some cases, each component of the binder resin is mixed as an emulsion before being combined with the other components and / or the glass fiber web. The divalent / trivalent metal may also be provided as an emulsion before being mixed with the binder and incorporated into the glass fiber web. In some embodiments, the components contained in the binder together with the divalent / trivalent metal may be pulled through the glass fiber web, for example, using gravity and / or vacuum. In some embodiments, one or more of the components contained in the binder resin and / or the divalent / trivalent metal may be diluted with soft water and pumped into the glass fiber web.
[0070] In some embodiments, the divalent / trivalent metals may be added after the binder and other ingredients have been added. For example, the divalent / trivalent metals may be introduced to the glass fiber web in a downstream step after the binder ingredients have already been introduced to the web. In another example, the divalent / trivalent metals may be introduced to the glass fiber web along with the binder, or one or more divalent / trivalent metals are added at the end of the process (e.g., before or after drying of the fiber web).
[0071] After the binder and divalent / trivalent metal are incorporated into the glass fiber web, the wet-laminate fibrous web may be appropriately dried. In some embodiments, the wet-laminate fibrous web may be drained. In some embodiments, the wet-laminate fibrous web may be passed through a series of drum dryers for drying at an appropriate temperature (e.g., 50°C to 150°C, or any other temperature suitable for drying). In some cases, the typical drying time may be varied until the moisture content of the composite fiber is as desired. In some embodiments, the drying of the wet-laminate fibrous web may be performed using infrared heaters. In some cases, the drying assists in hardening the fibrous web. In addition, the dried fibrous web may be appropriately wound for downstream filter media processing.
[0072] As an example, the filter medium can be prepared by a wet lamination process, in which a first dispersion (e.g., pulp) containing a glass fiber slurry (e.g., glass fibers in an aqueous solvent such as water) is applied onto a wire conveyor in a papermaking machine (e.g., Fourdrinier or Rotoformer®) to form a first phase. A second dispersion (e.g., another pulp) containing another glass fiber slurry (e.g., glass fibers in an aqueous solvent such as water) is then applied onto the first phase. A vacuum is continuously applied to the first and second dispersions of fibers during the above process to remove the solvent from the fibers, resulting in a filter medium having a first phase and a second phase. The formed filter medium is then dried. It can be understood that the filter medium can be suitably tailored not only based on the components of each glass fiber web, but also according to the effect of using multiple glass fiber webs of various properties in appropriate combination. In a contemplated embodiment, one or more of the glass webs contain glass fibers that have been treated to include additional divalent / trivalent metals.
[0073] After formation, the filter medium may be further processed according to various known techniques. For example, the filter medium may be pleated and used in a pleated filter element. In some embodiments, the filter medium or various layers thereof may be suitably pleated by forming score lines at appropriately spaced distances from each other to allow the filter medium to be folded. It should be understood that any suitable pleating technique may be used.
[0074] It should be understood that the filter medium may include other parts in addition to the glass fiber web. In some embodiments, the filter medium may include more than one glass fiber web. In some embodiments, further processing includes the incorporation of one or more structural features and / or stiffening elements. The glass fiber web may be combined with additional structural features, such as polymers and / or metal meshes. For example, a screen backing may be placed on the filter medium to provide additional stiffness. In some cases, the screen backing may help to hold the pleated configuration. For example, the screen backing may be an expanded metal wire or an extruded plastic mesh.
[0075] The filter media can be incorporated into a variety of suitable filter elements for use in a variety of applications, including ASHRAE filter media applications. The filter media can generally be used in any air filtration application. For example, the filter media can be used in heating and air conditioning ducts. The filter media can also be used in combination with other filters as a pre-filter, such as acting as a pre-filter for high efficiency filter applications (e.g., HEPA). The filter elements can have any suitable configuration known in the art, including bag filters and panel filters.
[0076] Treated filter substrate The process is thought to increase the affinity of the filter media for airborne viral particles, making such surfaces potentially beneficial in the fight against many viruses, including the Covid-19 virus.
[0077] Although existing glass HEPA filter media are known to effectively remove infectious agents such as viruses from the air, it is desirable to increase the affinity of the filter media for airborne objects. Once trapped, the infectivity of viral particles decays over a period of time, which can be several days (recently determined to be 5 days) on glass surfaces. Existing antiviral treatments of filter media tend to be thicker coatings that can degrade particle capture properties, and the treatments are usually multi-step processes that are not easily compatible with papermaking.
[0078] Filtration theories generally propose several particle capture mechanisms, including direct impaction of higher momentum particles, natural attraction of smaller, lower momentum particles to fiber surfaces, diffusion of submicron particles or stochastic contact with the media fibers, and electrostatic forces, with the primary mechanism being a function of the size of the particle being captured and its electrostatic or surface charge. There is a size range that is too small for any appreciable momentum effect, but too large for a major contribution from diffusion effects. This size range is called the Maximum Penetrating Particle Size (MPPS) and is typically in the 0.3 micron range for HEPA media.
[0079] For example, particle size distribution from aerosols generated by exhalation, combined with further variations in the liquid or mucus content of the inhaled particles, causes trapped bacteria- and virus-containing particles to penetrate the HEPA media to different depths as a function of the capture efficiency as described above. Prior art treatments are typically performed by spraying a coating of antimicrobial and antiviral species onto already manufactured HEPA media. These treatments are concentrated on one or both of the media's outer surfaces and do not effectively interact with particles that penetrate the media beyond the sprayed coating. Even antimicrobial coatings by immersion into pre-manufactured media are unlikely to uniformly treat the entire depth of the media, as interactions with the first encountered fibers may result in greater deposition of antimicrobial species, which may also result in uneven distribution.
[0080] In certain preferred embodiments of the present disclosure, a uniform distribution of divalent / trivalent metals is created throughout the thickness of the HEPA media, thereby maximizing the effectiveness of the media across the full range of possible microorganism-containing particle sizes and characteristics.
[0081] The metal-loaded C-glass samples discussed in the examples below were characterized by scanning electron microscopy. Energy dispersive X-ray spectroscopy (EDS or EDX) is a chemical microanalysis technique used in conjunction with scanning electron microscopy (SEM).
[0082] The well-dispersed metal treatment applied to glass in the present disclosure does not provide a coating or large aggregates (e.g., nanoparticles) that would alter the filtration performance of the filter media. Furthermore, while metal species are often not detectable using SEM techniques, the metal treatment of the present application is preferably uniformly distributed such that the metal species is present in a low enough amount so as not to obscure a significant percentage of the glass fiber surface. For example, as shown in Figure 3, the zinc-treated glass fiber surface is detectable and present in an amount that does not obscure the entire surface area of the fiber.
[0083] In some embodiments, metallization is performed to achieve various metal loading density ranges in atoms per square nanometer. 2 Metal loading density (atoms / nm2) for Ag, Cu, and Zn treatments on microglass fibers 2 ) and weight percent.
[0084] [Table 1]
[0085] In the illustrated embodiment, the metal is present in an amount ranging from 0.001 to 3.0% by weight of the fibrous substrate, preferably from 0.005 to 2.5% by weight of the fibrous substrate.
[0086] In some embodiments, the treated fibers have a density of 0.016 to 48 atoms / nm 2 , preferably 0.16 to 40 atoms / nm 2 The silver loading density ranges from 0.027 to 81 atoms / nm. 2 , preferably 0.27 to 67 atoms / nm 2 The zinc loading density may range from 0.026 to 79 atoms / nm 2 , preferably 0.26 to 66 atoms / nm 2 The range may be:
[0087] These and similar deposition techniques can also be used to apply metal ions to glass fibers at levels greater than 3.0 weight percent, however, at these higher levels the metal ions are increasingly deposited as oxides and hydroxides which typically result in less available form of metal.
[0088] Antibacterial and antiviral testing Because virus enumeration requires specialized skills and equipment to perform the analysis, as well as an exceptionally clean environment, bacterial surrogates are often used to determine the general bactericidal efficacy of antimicrobial treatments. This is particularly true for the use of vegetative Gram-negative bacteria and enveloped viruses, both of which have lipid bilayer cell envelopes that are targets of many biocides, such as metals and quaternary ammonium compounds. An example of this is Schmidt, Marcel, "Identification of potential bacterial surrogates for validation of thermal inactivation processes of hepatitis A virus." Master's Thesis, University of Tennessee, 2016. It is generally known that these bacterial surrogates are more resistant to biocides than their viral counterparts, and as a result, if an antimicrobial agent demonstrates efficacy against these surrogates, it is expected to have similar or better antibacterial activity against the corresponding enveloped virus. For example, a disinfectant that demonstrates virucidal activity against human coronaviruses within 30 seconds requires a 1-minute contact time to be effective against vegetative Gram-negative bacteria such as Serratia marcescens. Thus, the use of bacterial surrogates is a valid approach to ensure that biocides are similarly effective against the corresponding enveloped viruses.
[0089] Compared to an untreated surface of the substrate, the treated substrate is believed to have an increased affinity for airborne viral particles. EXAMPLES
[0090] Example I:C Copper on Glass Glass microfiber C-04-F from Unifrax is obtained. The as-received, unfired glass sample is then subjected to acid leaching treatment. 15 g of C-glass and 4 L of 5.5 wt% nitric acid are placed in a 4 L wide-mouth plastic container. The plastic container is placed in an airflow oven at 90°C for 2 hours and briefly shaken by hand every 30 minutes. After the acid leaching treatment is completed, the sample is filtered through a Buchner funnel fitted with a Whatman 541 filter paper of 150 mm diameter and washed with 7.6 L of deionized water. The acid leached sample is then dried at 110°C for 18 hours.
[0091] Second, the acid-leached C-glass is subjected to a metal loading treatment. In this example, copper nitrate is used to prepare 4 L of a 0.0006 wt.% copper solution in deionized water. 14 g of the acid-leached C-glass is added to the metal loading solution ("glass / metal solution mixture") in a 4 L wide-mouth plastic container. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted to above pH 10 by continuous dropwise addition of 29.8 wt.% ammonium hydroxide (NH4OH) (in this example, a pH of 10.4 is obtained). The container is placed in an airflow oven at 50°C for 2 hours and briefly shaken by hand every 30 minutes. After the metal loading treatment is completed, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a Whatman 541 filter paper with a diameter of 150 mm, and the collected glass sample is washed with 7.6 L of dilute NH4OH solution. A dilute NH4OH solution is prepared by mixing 10 g of concentrated 29.8 wt% NH4OH solution with 3.8 L of deionized water. The metal-loaded glass sample is then dried at 110 °C for 18 h.
[0092] Analysis of the sample by ICP-AES gives a copper concentration of 0.080 wt.%.
[0093] Another similarly prepared sample analyzed by ICP-AES gives a copper concentration of 0.094% by weight. The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.6% reduction after 4 hours of exposure versus the control sample (untreated fiber) which shows a 36.9% reduction.
[0094] Example II: Silver on Glass Glass microfiber C-04-F from Unifrax is obtained. The as-received, unfired glass sample is then subjected to acid leaching treatment. 12 g of C-glass and 4 L of 5.5 wt% nitric acid are each placed in a 4 L wide-mouth plastic container. The plastic container is placed in an airflow oven at 90°C for 2 hours and briefly shaken by hand every 30 minutes. After the acid leaching treatment is completed, the sample is filtered through a Buchner funnel fitted with a Whatman 541 filter paper of 150 mm diameter and washed with 7.6 L of deionized water. The acid leached sample is then dried at 110°C for 18 hours.
[0095] Second, the acid-leached C-glass is subjected to a metal loading treatment. In this example, silver nitrate is used to prepare 4 L of a 0.001 wt% silver solution in deionized water. 11 g of the acid-leached C-glass is added to the metal loading solution ("glass / metal solution mixture") in a wide-mouth plastic container. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted to above pH 10 by continuous dropwise addition of 29.8 wt% ammonium hydroxide (NH4OH) (in this example, a pH of 10.4 is obtained). The container is placed in a 50°C oven airflow oven for 2 hours and briefly shaken by hand every 30 minutes. After the metal loading treatment is completed, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a 150 mm diameter Whatman 541 filter paper, and the collected glass sample is washed with 7.6 L of dilute NH4OH solution. A dilute NH4OH solution is prepared by mixing 10 g of concentrated 29.8 wt% NH4OH solution with 3.8 L of deionized water. The metal-loaded glass sample is then dried at 110 °C for 18 h.
[0096] Analysis of the sample by ICP-AES gives a silver concentration of 0.19 wt %.
[0097] Another similarly prepared sample analyzed by ICP-AES gives a silver concentration of 0.15% by weight. The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.4% reduction after 4 hours exposure versus the control sample which shows a 36.9% reduction.
[0098] Example III: Copper and Silver on Glass Glass microfiber C-04-F from Unifrax is obtained. First, the as-received, unfired glass sample is subjected to acid leaching treatment. 15 g of C-glass and 4 L of 5.5 wt% nitric acid are placed in a 4 L wide-mouth plastic container. The plastic container is placed in an airflow oven at 90 °C for 2 hours and briefly shaken by hand every 30 minutes. After the acid leaching treatment is completed, the sample is filtered through a Buchner funnel fitted with a Whatman 541 filter paper of 150 mm diameter and washed with 7.6 L of deionized water. The acid leached sample is then dried at 110 °C for 18 hours.
[0099] Second, the acid-leached C-glass is subjected to a metal loading treatment. In this example, 4 L of a 0.0016 wt.% total metal solution in deionized water is used. The metal loading solution is prepared by mixing 2 L of a 0.001 wt.% silver solution with 2 L of a 0.0006 wt.% copper solution. In this example, silver nitrate is used to prepare 2 L of a 0.001 wt.% M1 solution, and copper nitrate is used to prepare 2 L of a 0.0006 wt.% M2 solution. 13 g of the acid-leached C-glass is added to the metal loading solution ("glass / metal solution mixture") in a wide-mouth plastic container. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted to above pH 10 (in this example, a pH of 10.4 is obtained) by continuous dropwise addition of 29.8 wt.% ammonium hydroxide (NH4OH). The container is placed in a 50°C oven airflow oven for 2 hours and briefly shaken by hand every 30 minutes. After the metal loading process is completed, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a 150 mm diameter Whatman 541 filter paper, and the collected glass sample is washed with 7.6 L of dilute NH4OH solution, which is prepared by mixing 10 g of concentrated 29.8 wt% NH4OH solution with 3.8 L of deionized water. The metal-loaded glass sample is then dried at 110 °C for 18 h.
[0100] Analysis of the sample by ICP-AES gives a silver concentration of 0.15 wt.% and a copper concentration of 0.05 wt.%.
[0101] The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.8% reduction after 4 hours of exposure versus the control sample showing a 36.9% reduction.
[0102] Example IV: Zinc on C-glass Glass microfiber C-04-F from Unifrax is obtained. First, the as-received, unfired glass sample is subjected to acid leaching treatment. 15 g of C-glass and 4 L of 5.5 wt% nitric acid are placed in a 4 L wide-mouth plastic container. The plastic container is placed in an airflow oven at 90 °C for 2 hours and briefly shaken by hand every 30 minutes. After the acid leaching treatment is completed, the sample is filtered through a Buchner funnel fitted with a Whatman 541 filter paper of 150 mm diameter and washed with 7.6 L of deionized water. The acid leached sample is then dried at 110 °C for 18 hours.
[0103] Second, the acid-leached C-glass is subjected to a metal loading treatment. In this example, zinc nitrate hexahydrate is used to prepare 4 L of a 0.0005 wt.% zinc solution in deionized water. 14 g of the acid-leached C-glass is added to the metal loading solution ("glass / metal solution mixture") in a 4 L wide-mouth plastic container. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted to above pH 10 by continuous dropwise addition of 29.8 wt.% ammonium hydroxide (NH4OH) (in this example, a pH of 10.2 is obtained). The container is placed in a 50°C oven airflow oven for 2 hours and briefly shaken by hand every 30 minutes. After the metal loading treatment is completed, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a 150 mm diameter Whatman 541 filter paper, and the collected glass sample is washed with 7.6 L of dilute NH4OH solution. A dilute NH4OH solution is prepared by mixing 10 g of concentrated 29.8 wt% NH4OH solution with 3.8 L of deionized water. The metal-loaded glass sample is then dried at 110 °C for 18 h.
[0104] Analysis of the sample by ICP-AES gives a zinc concentration of 0.14 wt.%.
[0105] The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.5% reduction after 4 hours of exposure versus the control sample showing a 36.9% reduction.
[0106] Example V:B Copper on Glass Glass microfiber B-04-F from Unifrax is obtained. The B glass is subjected to a metal loading treatment. In this example, 1.2 L of a 0.025 wt.% copper solution is prepared in tap water using copper (II) sulfate pentahydrate. 12 g of chopped B glass is added to the metal loading solution ("glass / metal solution mixture") in a 2 L plastic beaker. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted by adding 0.1 M NaOH (about 30 mL, which in this example results in a pH of 5.7). The glass / metal solution mixture is then stirred at room temperature for 15 minutes using an overhead mixer and a circular steel impeller. After the metal loading treatment is complete, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a Whatman 541 filter paper with a diameter of 150 mm. The metal-loaded glass sample is then dried at 100°C for 3 hours.
[0107] Analysis of the sample by ICP-AES gives a copper concentration of 2.02 wt.%.
[0108] Example VI: B Zinc on Glass Glass microfiber B-04-F from Unifrax is obtained. The B glass is subjected to a metal loading treatment. In this example, zinc sulfate heptahydrate is used to prepare 1.2 L of a 0.0191 wt. % zinc solution in tap water. 12 g of chopped B glass is added to the metal loading solution ("glass / metal solution mixture") in a 2-L plastic beaker. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted by adding 0.1 M NaOH (about 40 mL, which in this example results in a pH of 8). The glass / metal solution mixture is then stirred at room temperature for 15 minutes using an overhead mixer and a circular steel impeller. After the metal loading treatment is complete, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a Whatman 541 filter paper with a diameter of 150 mm. The metal-loaded glass sample is then dried at 1100°C for 3 hours.
[0109] Analysis of the sample by ICP-AES gives a net zinc concentration increase of 2.0 wt.%.
[0110] Example IX: B Zinc on Glass Glass microfiber B-04-F from Unifrax is obtained. The B glass is subjected to a metal loading process. In this example, zinc nitrate hexahydrate is used to prepare 1.867 L of a 0.00244 wt. % zinc solution in deionized water. 7 g of chopped B glass is added to the metal loading solution ("glass / metal solution mixture") in a 2-L plastic beaker. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted to above pH 10 by continuous dropwise addition of 29.8 wt. % ammonium hydroxide (NH4OH) (a pH of 10.3 is obtained in this example). The glass / metal solution mixture is then stirred at room temperature for 30 minutes using an overhead mixer and a circular steel impeller. After the metal loading process is completed, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a Whatman 541 filter paper with a diameter of 150 mm and washed with 3.547 L of deionized water. The metal-loaded glass samples are then dried in an airflow oven at 110° C. for 18 hours.
[0111] Analysis of the sample by ICP-AES gives a net zinc concentration increase of 0.58 wt.%.
[0112] The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.5% reduction after 4 hours of exposure versus the control sample showing a 0% reduction.
[0113] Example X:B Zinc on Glass Obtain glass microfiber B-04-F from Unifrax. Subject the B glass to a metal loading treatment. In this example, prepare 800 mL of a 0.00375 wt.% zinc solution in deionized water using zinc nitrate hexahydrate. Add 3 g of shredded B glass to the metal loading solution ("glass / metal solution mixture") in a 1 L plastic bottle. Measure the pH of the glass / metal solution mixture. If necessary, adjust the pH of the mixture to above pH 10 by continuous dropwise addition of 29.8 wt.% ammonium hydroxide (NH4OH) (a pH of 10.2 is obtained in this example). Place the container under a hood at room temperature for 30 minutes, occasionally shaking briefly by hand. After the metal loading treatment is complete, filter the glass / metal solution mixture through a Büchner funnel fitted with a Whatman 541 filter paper 150 mm in diameter and wash with 1.52 L of deionized water. The metal-loaded glass sample is then dried in an airflow oven at 110 °C for 18 hours.
[0114] Analysis of the sample by ICP-AES gives a net zinc concentration increase of 0.93 wt.%.
[0115] The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.6% reduction after 4 hours of exposure versus the control sample showing a 0% reduction.
[0116] Example XI:B Copper on Glass Glass microfiber B-04-F from Unifrax is obtained. The B glass is subjected to a metal loading process. In this example, 1.867 L of a 0.00244 wt % copper solution is prepared in deionized water using copper (II) nitrate hemi-pentahydrate. 7 g of chopped B glass is added to the metal loading solution ("glass / metal solution mixture") in a 2-L plastic beaker. The pH of the glass / metal solution mixture is measured. If necessary, the pH of the mixture is adjusted to above pH 10 by continuous dropwise addition of 29.8 wt % ammonium hydroxide (NH4OH) (a pH of 10.2 is obtained in this example). The glass / metal solution mixture is then stirred at room temperature for 30 minutes using an overhead mixer and a circular steel impeller. After the metal loading process is completed, the glass / metal solution mixture is filtered through a Buchner funnel fitted with a 150 mm diameter Whatman 541 filter paper and washed with 3.547 L of deionized water. The metal-loaded glass samples are then dried in an airflow oven at 110° C. for 18 hours.
[0117] Analysis of the sample by ICP-AES gives a copper concentration of 0.57 wt.%.
[0118] The virucidal properties of this material against human coronavirus strain 229E (ATCC#VR-740) analyzed by ISO 18184:2019(E) show a 99.8% reduction after 4 hours of exposure versus the control sample showing a 0% reduction.
[0119] Example XII. SARS-CoV-2 and H1N1 Testing A Zn-treated glass was made using a procedure similar to that of Example IX, except that the Zn target was lower and the pH was adjusted to 9. The resulting fibers had a Zn level measured by ICP of 0.2 wt %.
[0120] Antiviral activity in ISO 1848 testing with SARS-CoV-2 virus resulted in a 98.4% reduction vs. the control sample. Antiviral activity in ISO 1848 testing with Influenza A virus (H1N1) resulted in a 98.1% reduction vs. the control sample.
[0121] The Cu-treated glass of Example XI was evaluated in the same test and showed a 99.7% and 98.5% reduction versus the control for SARS-CoV-2 and Influenza A virus (H1N1), respectively.
[0122] Affinity testing of airborne particles Filters with media treated with the same relative proportions of zinc as in Example X, but run on a pilot paper machine pulper and adjusted to a pH of 8-9 using NaOH solution, yielded an average Zn2+ loading of 0.82 wt. %, and filters with untreated media were used to produce two filters, each measuring 24 x 24 x 2". Both treated and untreated media contained a mixture of different sized fibers. The untreated media was a glass microfiber MERV 13 HVAC filter manufactured under substantially similar manufacturing conditions as the treated media. Filters were manufactured by pleating the treated and untreated media and gluing both pleated media to a beverage board frame so that they could be installed in an ASHRAE test duct. For single pass efficiency testing, aerosolized MS-2 bacteriophage (ATCC 15597-B1) was used as the test aerosol organism.
[0123] Single-pass efficiency test: Organisms were grown on appropriate media, harvested, and resuspended in saline to 5 x 10E7 pfu / mL. The organism suspension was then aerosolized into the test duct using a nebulizer. Both upstream and downstream air samples were taken using an SKC Bio-Stage Impactor calibrated to 28.3 L / M while the test aerosol was injected into the test duct. The recovery plates, with a double layer of agar medium consisting of a hard Lysogeny broth (LB) underlayer and a soft top layer incorporating E. coli, were then incubated for 24 hours at 35°C (95°F) and 96% relative humidity. After incubation, the recovered plaque-forming units (PFU) were counted. Only PFUs 1.0 mm or larger were counted. Efficiency was calculated using the following formula:
[0124]
number
[0125] Test conditions and equipment Single-pass efficiency tests were conducted in a 24 x 24 ASHRAE duct. The test system airflow was run at 1000 cfm. The horizontal stainless steel test duct was constructed in accordance with ASHRAE Standard 52.2-2017, Method of Testing General Ventilation Air-Cleaning Devices for Removal Efficiency by Particle Size. See Zhang, et al., "Study of Viral Filtration Performance of Residential HVAC Filters," FIG. 1, ASHRAE Journal (August 2020).
[0126] The viral reduction occurring in the test apparatus without the filter present was recorded upstream and downstream of the filter mount. The data from the test are shown in the table below.
[0127] [Table 2]
[0128] [Table 3]
[0129] [Table 4]
[0130] [Table 5]
[0131] As can be seen above, the results showed that filters made from untreated filter media had removal efficiencies of 31.0-34.7%. In contrast, filters made using filter media treated to increase the loading of divalent metals showed removal efficiencies of at least 77% and up to 86%. After completion of the aforementioned experiments, it was believed that the results using untreated filter media may be unreliable due to the experimental conditions.
[0132] Therefore, another similar experiment was performed and the following data was collected.
[0133] [Table 6]
[0134] As can be seen above, filters made from untreated media had an average removal efficiency of 79.4%. In contrast, filters made with media treated to increase divalent metal loading showed an average removal efficiency of 93.8%.
[0135] Multipass Efficiency Test: Multipass efficiency tests were performed using MS-2 bacteriophage (ATCC 15597-B1) as the challenge aerosol. The tests were performed in a large (4000 ft 3 ) in a stainless steel chamber.
[0136] In these tests, MS-2 bacteriophage was collected and 10E 9 pfu / mL. A nebulizer was then used to aerosolize a suspension of organisms into the chamber before powering the test apparatus. The test chamber air was sampled at 10 minute intervals for 1 minute sampling periods using an SKC Bio-Stage cascade impactor while circulating the chamber air through a wrap-around test duct containing a test filter. The cascade impactor was calibrated to an air flow rate of 28.3 liters / min and the sampling inlet was placed away from the midpoint of the test chamber. After 24 hours of incubation, the recovered organisms were counted. The circulation times and associated removal efficiencies are shown in the table below.
[0137] The corrected removal efficiency of the air cleaner uses the empty chamber data from time=0 as follows:
[0138]
number
[0139] The average removal efficiency for triplicate experiments using three treated and untreated filters at various circulation times was determined as follows:
[0140] [Table 7]
[0141] As can be seen from the above data in Table 7, the treated filters removed viral aerosols from the chamber more quickly than the untreated filters, as shown by 62.43% removal by the treated filters in 30 minutes and 47.93% removal by the untreated filters after 30 minutes.
[0142] In a similar experiment, the filter was preloaded with dust before the viral aerosol removal test. The efficiency of the viral aerosol removal efficiency at different circulation times was determined as follows:
[0143] [Table 8]
[0144] [Table 9]
[0145] In this experiment, the viral aerosol removal efficiency of the treated dust-loaded filters reached relatively high values significantly faster than the untreated dust-loaded filters, even after circulation through the filters for as short as 5 minutes.
[0146] Specific Embodiments While the following will be described in conjunction with specific embodiments, it will be understood that this description is illustrative, but is not intended to limit the scope of the foregoing description and appended claims.
[0147] A first embodiment of the present invention is a process for treating a fiber substrate comprising: providing a fiber substrate comprising glass fibers; introducing the fiber substrate into a salt solution, the salt solution comprising divalent metal cations, trivalent metal cations, or a combination thereof; depositing the metal cations on the fiber substrate; and drying the fiber substrate after the metal cations have been deposited, wherein the divalent metal cations and the trivalent metal cations are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, La3+, Bi3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, Lu3+. An embodiment of the present invention is any one, any or all of the first embodiment to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, and Ba2+. An embodiment of the present invention is any one, any or all of the first embodiment to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation are deposited by ion exchange. An embodiment of the present invention is any one, any or all of the first embodiment to the previous embodiment of this paragraph, in which the ion exchange is performed with protons on the fiber substrate. An embodiment of the present invention is any one, any or all of the first embodiment to the previous embodiment of this paragraph, in which the ion exchange is performed with monovalent metal cations on the fiber substrate. An embodiment of the present invention is any one, any or all of the first embodiment of this paragraph through the previous embodiment of this paragraph, in which the divalent metal cations and the trivalent metal cations are deposited by entanglement in the fiber substrate. An embodiment of the present invention is any one, any or all of the first embodiment of this paragraph through the previous embodiment of this paragraph, further comprising increasing the amount of SiOH species on the glass fiber.An embodiment of the invention is one, any, or all of the first embodiment to the previous embodiment of this paragraph, in which the amount of SiOH is increased by acid leaching. An embodiment of the invention is one, any, or all of the first embodiment to the previous embodiment of this paragraph, in which the acid leaching is performed before introducing the fiber substrate into the salt solution. An embodiment of the invention is one, any, or all of the first embodiment to the previous embodiment of this paragraph, in which the acid leaching is performed simultaneously with introducing the fiber substrate into the salt solution. An embodiment of the invention is one, any, or all of the first embodiment to the previous embodiment of this paragraph, in which the amount of the divalent metal cations and the trivalent metal cations on the fiber substrate is increased by at least 0.001% by weight of the fiber substrate. An embodiment of the invention is one, any, or all of the first embodiment to the previous embodiment of this paragraph, in which the amount of the divalent metal cations and the trivalent metal cations on the fiber substrate is at least 0.005% by weight of the fiber substrate. An embodiment of the present invention is any one, any or all of the first embodiment in this paragraph to the previous embodiment in this paragraph, in which the amount of the divalent metal cations and the trivalent metal cations on the fiber substrate is 0.001 to 3.0 weight % of the fiber substrate.
[0148] A second embodiment of the invention is a filter media substrate comprising glass fibers, the glass fibers being treated to increase the amount of divalent cations, trivalent cations, or both by at least 0.001% by weight, and the divalent metal cations and the trivalent metal cations are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, Bi3+, La3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, and Lu3+. The embodiment of the present invention is one, any, or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, and Ba2+.The embodiment of the present invention is one, any, or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation constitute 0.005-3.0% by weight of the filter medium substrate.The embodiment of the present invention is one, any, or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation constitute 0.01-3.0% by weight of the filter medium substrate. The embodiment of the present invention is one, any, or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation constitute 0.05-3.0% by weight of the filter medium substrate.The embodiment of the present invention is one, any, or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation constitute 0.1-3.0% by weight of the filter medium substrate.The embodiment of the present invention is one, any, or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, in which the divalent metal cation and the trivalent metal cation constitute 0.15-3.0% by weight of the filter medium substrate.
[0149] Without further elaboration, it is believed that, using the preceding description, one skilled in the art can utilize the present invention to its fullest extent and easily ascertain the essential characteristics of the present invention without departing from the spirit and scope of the present invention, and can make various changes and modifications to the present invention to adapt it to various uses and conditions. The preceding preferred specific embodiments are therefore to be construed as merely illustrative, and are not limitative of the remainder of the disclosure in any way, but are intended to cover various modifications and equivalent arrangements falling within the scope of the appended claims.
[0150] Above, all temperatures are set forth in degrees Celsius and all parts and percentages are by weight unless otherwise stated.
[0151] In the above detailed description of the present invention, at least one exemplary embodiment has been presented, but it should be understood that a vast number of variations exist. It should also be understood that the exemplary embodiment(s) are merely examples, and are in no way intended to limit the scope, applicability, or configuration of the present invention. Rather, the above detailed description provides those skilled in the art with a convenient guide for implementing the exemplary embodiments of the present invention, and it should be understood that various changes may be made in the functions and arrangement of elements described in the exemplary embodiments without departing from the scope of the present invention as set forth in the appended claims and their legal equivalents.
Claims
1. 1. A process for treating a textile substrate, comprising: Providing a fiber substrate comprising glass fibers (102); Introducing the fiber substrate into a salt solution (106), the salt solution including divalent metal cations, trivalent metal cations, or a combination thereof (106); depositing the metal cations on the fiber substrate; drying the fiber substrate after the metal cations have been deposited (112); and Including, 3+, wherein the divalent metal cations and the trivalent metal cations are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, La3+, Bi3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, and Lu3+, preferably, the divalent metal cations and the trivalent metal cations are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, and Ba2+.
2. 2. The process of claim 1, wherein the divalent metal cations and the trivalent metal cations comprise 0.005 to 3.0% by weight of the filter media substrate, or 0.01 to 3.0% by weight, or 0.05 to 3.0% by weight, or 0.1 to 3.0% by weight.
3. 3. The process of claim 1 or claim 2, wherein the divalent metal cations and the trivalent metal cations are deposited by ion exchange.
4. The process of claim 3 , wherein the ion exchange is performed with protons on the fiber substrate.
5. The process of claim 3 , wherein the ion exchange is performed with a monovalent metal cation on the fibrous substrate.
6. 3. The process of claim 1 or claim 2, wherein the divalent metal cations and the trivalent metal cations are deposited by entanglement in the fibrous substrate.
7. 3. The process of claim 1 or claim 2, further comprising increasing the amount of SiOH species on the glass fibers.
8. 8. The process of claim 7, wherein the amount of SiOH is increased by acid leaching (104).
9. 9. The process of claim 8, wherein the acid leaching (104) occurs prior to or simultaneously with introducing the fibrous substrate into the salt solution (106).
10. A filter medium substrate, comprising: glass fibers that have been treated to increase the amount of divalent cations, trivalent cations, or both by at least 0.001% by weight; The divalent metal cation and the trivalent metal cation are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, Ba2+, Bi3+, La3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, and Lu3+, and preferably, the divalent metal cation and the trivalent metal cation are selected from the group consisting of Mn2+, Co2+, Co3+, Ga3+, Al3+, Mg2+, Ca2+, Sr2+, and Ba2+; The filter medium substrate, wherein the divalent metal cations and the trivalent metal cations constitute 0.005 to 3.0 wt.%, or 0.01 to 3.0 wt.%, or 0.05 to 3.0 wt.%, or 0.1 to 3.0 wt.%.
Citation Information
Patent Citations
Special filtering material for dust removal in waste incineration
CN109173436A
Normal-temperature catalyst, composite filtering screen and application of composite filtering screen
CN109603853A
Preparation method of glass fiber filter element, glass fiber filter element and air filter element product
CN111495038A
A low weight resistant porous glass fiber having physical, chemical or biological properties
EP1044935A1
JP1975095596A